The Berry phase in graphene and graphite multilayers: Graphene and graphite multilayers - Mikitik, G.P.; Sharlai, Yu.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
We discuss the electron energy spectra and the Berry phases for graphene, a graphite bilayer, and bulk graphite allowing for a small spin-orbit interaction. If an electron orbit in the Brillouin zone surrounds several Dirac points (band-contact lines in graphite), one can find relative signs of the Berry phases generated by these points (lines) by taking into account this interaction.